Kebutuhan Perawatan Ortodonti Berdasarkan Karakteristik Demografi - Kirana Damayanti, Nasywa; Kusnoto, Joko; Hapsari Andayani, Lia (Jurnal Kedokteran Gigi Terpadu, 2025)
Malocclusion is a functional disorder that can negatively impact a person’s physical and emotional health, often requiring treatment. The prevalence of malocclusion in Indonesia is approximately 80% of the total population, making it a significant dental health issue. According to the Health Research and Development Agency of the Ministry of Health of the Republic of Indonesia (Balitbangkes RI), the highest prevalence is found in the 12-15 age group, at 15.6%. Orthodontic treatment aims to correct improve function, facial aesthetics, and occlusal contact. The need for treatment can be assessed using the Orthodontic Treatment Needs Index (IKPO), which evaluates the severity of malocclusion based on three variables: knowledge, awareness, and willingness. Demographic factors such as gender, age, economic status, and administrative region can influence access to orthodontic services. Differences in demographic characteristics can lead to differences in knowledge, attitudes, and actions towards dental health, including malocclusion. It is important to improve education about oral health and ensure equal access to orthodontic treatment, especially in underserved areas.